KENYAMANAN FURNITUR KELAS B DI TK AISYIYAH 61 SERENGAN BERDASAR ERGONOMI DAN ANTROPOMETRI - Putri Sekar Hapsari (Gelar : Jurnal Seni Budaya, 2011)
Tables, chairs and shelves son is a furniture that is used as a means of supporting a very important role in the smooth implementation of the child’s learning process. Inconsistency between the size of the furniture to the size of a child’s body is one of the obstacles in improving the quality of human resources. As a result of the tables and chairs are not in accordance with the child’s body size can lead to children experiencing rapid fatigue, impact for long periods can also cause health problems. This study aims to determine the extent of the child’s body size in accordance with furniture provided. Anthropometric measurements are very important to see if the furniture is ergonomic. Furniture tables, chairs and shelves children the focus of research because it is the furniture that intersect directly with the children when they make the learning process in class. The method used in descriptive qualitative and quantitative approaches, or can also be called a dual research strategy using a variety of methods to solve a research problem. Quantitative here uses numerical data observations in the field of measurement, then being compared with the references that used and next it is analyzed based on researchers interpretation that are from field analysis. The results showed that anthropometry size in use in the manufacture of furniture in general is in conformity with the size of children aged six to seven years, there is little record of the width of the table needs to be added, as well as the pelvis and the seat backrest seat needs to be adjusted to the shape of the bone pelvis and spine, or given soft foam to make it more comfortable to wear in a longer time. Rack size is in accordance with a range of children.Key words : Anthropometry, Ergonomics, Furniture, early childhood